2010
DOI: 10.1177/0734904110386187
|View full text |Cite
|
Sign up to set email alerts
|

Thermocouple Response in Fires, Part 1: Considerations in Flame Temperature Measurements by a Thermocouple

Abstract: This PIRT exercise identifies a number of factors which can influence thermocouple readings made in fires. Identified factors are: (a) the fuel/oxidizer equivalence ratio and its effect on readings, (b) the influence of the state of oxidation and variation with time for the thermocouple sheath, (c) the convection coefficient models and how experimental readings are influenced by thermocouple diameter and yaw angle, (d) response time of a MIMS thermocouple, and (e) thermocouple end effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…These results are reflective of the modeling intent -to compare the output of the thermocouple model, to experiment and to achieve a large region of uniform temperature surrounding the thermocouple There is remarkable agreement between the thermocouple temperature prediction and observed thermocouple response, as demonstrated in Validation of Virtual Thermocouple Model for Fire Codes simulation values represented by the red triangles in Figure 8 (and the results shown in Figure 5) were calculated using the temperaturedependent emissivity [7]. The actual diameters of the thermocouple probes were not measured, and the uncertainty in diameter is also propagated through the numerical results.…”
Section: Computational Results and Validationmentioning
confidence: 72%
“…These results are reflective of the modeling intent -to compare the output of the thermocouple model, to experiment and to achieve a large region of uniform temperature surrounding the thermocouple There is remarkable agreement between the thermocouple temperature prediction and observed thermocouple response, as demonstrated in Validation of Virtual Thermocouple Model for Fire Codes simulation values represented by the red triangles in Figure 8 (and the results shown in Figure 5) were calculated using the temperaturedependent emissivity [7]. The actual diameters of the thermocouple probes were not measured, and the uncertainty in diameter is also propagated through the numerical results.…”
Section: Computational Results and Validationmentioning
confidence: 72%
“…For the sake of safety, a flash arrester was used between the mixer and the flow meter of hydrogen. Moreover, a K-type thermocouple with a bead diameter of 0.5 mm was used to measure the exhaust gas temperature, and the temperature presented in this paper has been corrected considering the heat losses to the ambient [32]. A digital camera was used to take flame pictures from the top viewpoint.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…Previously, CARS measurements also showed that Hencken burners are nearly adiabatic. 3,4 The grid was generated using polyhedral cell elements to create a conformal multiregion to allow heat transfer between solids and fluids. Figure 3 shows the grid and the detailed thermocouple surrounded by boundary-layer prism cells.…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…The virtual thermocouple model in Vulcan and experimental validation based on well-established flame experiments, using a Hencken burner, various sizes of thermocouples, and Coherent Anti-Stokes Raman Spectroscopy (CARS), are discussed in detail for MIMS thermocouples. 3,4 To supplement these earlier research investigations, detailed multiphysics modeling 5 was performed using a commercial code STAR-CCM + . 6 Although Vulcan and STAR-CCM + have similar physical modeling capabilities, the commercial code has more versatile meshing capabilities, which is an advantage when complex, multiregion grids are needed.…”
Section: Introductionmentioning
confidence: 99%